Des elephants et des hommes. Etude de cas: les populations d’elephants d’Alfakoara (nord-est du Benin) - Sournia, Gerard (Pachyderm, 1993)
Describes a plan to share a water resource between a small herd of elephants and villagers and their domestic stock. The village of Alfakoara is situated in north eastern Benin near the border with Niger. The elephants consisting of several dozen of various ages visit a depression near the village on a daily basis. Except for the dry months of January to March the depression contains sufficient water for both the villagers and the elephants who have developed a tolerance of each other and a sharing of the water resource. The article outlines a programme to deepen and enlarge the depression , and to build a viewing stand for eco tourism development.